Correlation of bleeding pattern with endometrial histopathologic results in perimenopausal women with abnormal uterine bleeding - Yilmaz, Zehra; Yilmaz, Elif Akkas; Cakmak, Bulent; Gultekin, Ismail Burak; Karsli, Mehmet Fatih; Cekmez, Yasemin; Kara, Osman Fadil; Kucukozkan, Tuncay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal Uterine Bleeding (AUB) is referred as bleeding outside of normal menstruation pattern and it is the most common gynecological problem for women of all ages. This study was evaluated the correlation of menstrual bleeding patterns and endometrial histopathological findings in perimenopausal women. Methods: This study was done on perimenopausal aged women presented with AUB for the last 6 months at a gynecology clinic of a tertiary medical center. Only the patients with isolated endometrial causes of AUB were selected for study. A total of 313 cases were included in the study. Abnormal bleeding patterns of the patients were recorded and endometrial sampling was performed to all women. AUB was classified as menorrhagia, metrorrhagia, menometrorrhagia, polymenorrhea, intermenstrual bleeding, and histopathological findings were classified as Proliferative Endometrium (PE), Secretory Endometrium (SE), Disordered Proliferative Pattern (DPP), Endometrial Polyp (EP), Chronic Endometritis (CE), Endometrial Hyperplasia (EH), and Endometrial Adenocarcinoma (CA). Results: The most common bleeding pattern was menorrhagia (45.0%) and the most common histopathological finding was PE+SE (52.0%) in our study. PE+SE and endometrial hyperplasia without atypia were found more common in menorrhagia group. The most histopathological findings were found PE+SE in menometrorrhagia and polymenorrhea group (P <0.001). Although EP and CE were observed more common in intermenstrual bleeding group (P <0.001), there were no statistically significant difference in endometrial histopathological findings in metrorrhagia group (P >0.05). Conclusions: We concluded that although menometrorrhagia and polymenorrhea were significantly more associated with PE+SE, intermenstrual bleeding was significantly more associated with EP and CE. It is noteworthy that endometrial hyperplasia without atypia is significantly higher in patients with menorrhagia which is the most common abnormal bleeding pattern in perimenopausal aged women.